Severity of oxidative stress in patients with co-infection tuberculosis/HIV with lymphopenia - Kothapalli, M. K. (Запорізький державний медичний університет, 2021)
Aim. To determine the severity of oxidative stress in patients with co-infection tuberculosis/HIV with lymphopenia. Materials and methods. We examined 41 patients with tuberculosis/HIV co-infection, who were treated in Zaporizhzhia regional phthisio-pulmonological clinical centre during last 3 years. Patients were divided in 2 groups.